EXECUTION OF CONFISCATION OF FIDUCIARY SECURITY OBJECTS DUE TO CUSTOMERS UNABLE TO PAY INSTALMENTS - Nur Nafisah (JURISTA: Jurnal Hukum dan Keadilan, 2017)
Fiduciary guarantee is a transfer of ownership rights of an object on the basis of trust with the provision that the object whose ownership rights are transferred remains in the possession of the owner of the object. This research is focused on knowing how the mechanism for confiscating collateral objects due to customers unable to pay instalments at PT Mandiri Tunas Finance Banda Aceh? The method used is qualitative with descriptive analysis, namely researching problems based on the focus and object of research. The results of this study indicate that: the execution of the object of fiduciary guarantee at PT Mandiri Tunas Finance is carried out against debtors who are in arrears in paying monthly instalments by withdrawing the object of fiduciary guarantee from the hands of the debtor, the execution at PT Mandiri Tunas Finance is carried out by internal finance as a collector and external parties, then the results of the execution of the guarantee are sold under the hand and through a public auction used to pay off the remaining debts of the debtor. The implementation of execution at PT Mandiri Tunas Finance with debtors who are delinquent in paying monthly instalments makes the implementation of parate execution not carried out as it should, thus making one party feel disadvantaged, both from PT Mandiri Tunas Finance and the customer.